Epidemiological and Clinical Characteristics of Pediatric Acute Drug Intoxications: A Retrospective Analysis - Cristina Elena Singer; Renata-Maria Văruț; Maria Singer; Simona Cosoveanu; Jaqueline Abdul Razzak; Madalina Elena Popescu; Simina Gaman; Ileana Octavia Petrescu; Cristina Popescu (Children)
Background/Objectives: Acute drug intoxications (ADIs) are a significant concern in pediatric healthcare, contributing to both accidental and intentional morbidity. This study aimed to analyze the demographic, clinical, and therapeutic characteristics of pediatric ADI cases to identify trends and inform preventive strategies. Methods: This retrospective study included 120 cases of pediatric ADI admitted to the Second Pediatric Clinic of Craiova County Emergency Clinical Hospital in 2022 and 2023. The inclusion criteria encompassed children aged 0–17 years with confirmed pharmaceutical intoxications. Cases involving mixed poisonings or non-pharmaceutical substances were excluded. Clinical severity was classified using the Poisoning Severity Score (PSS). Data on demographics, substances involved, clinical presentations, interventions, and outcomes were analyzed. Results: The majority of cases occurred in females (73.3%) and urban residents (77.5%). Accidental intoxications were prevalent in children aged 1–5 years (45%), while intentional ingestions were common in adolescents (47.5%). The most frequently implicated substances included antibiotics (46.7%), benzodiazepines (20.8%), and acetaminophen (15.8%). Severity was classified as mild (44.2%), moderate (26.6%), or severe (29.2%), while treatment primarily included supportive care, intravenous fluids (62.5%), and antidotes (35.8%). Severe cases required respiratory support in 29.2% of the instances. Hospitalization duration significantly decreased from 2022 (3.8 ± 1.9 days) to 2023 (2.3 ± 0.9 days) (p < 0.05), and no fatalities were recorded. Conclusions: Pediatric ADIs predominantly involve accidental ingestions in young children and intentional overdoses in adolescents. Targeted public health strategies, such as parental education, adolescent mental health support, and improved rural healthcare access, are essential to reduce incidence and severity. These findings underscore the need for focused prevention and optimized clinical management.